How Projective is Projective Content? Gradience in Projectivity and At-issueness. (28th June 2018) - Tonhauser, Judith; Beaver, David I; Degen, Judith
Abstract: Projective content is utterance content that a speaker may be taken to be committed to even when the expression associated with the content occurs embedded under an entailment-canceling operator (e.g., Chierchia & McConnell-Ginet, 1990 ). It has long been observed that projective content varies in how projective it is (e.g., Karttunen, 1971 ; Simons, 2001 ; Abusch, 2010 ), though preliminary experimental research has been able to confirm only some of the intuitions about projection variability (e.g., Smith & Hall, 2011 ; Xue & Onea, 2011 ). Given the sparse empirical evidence for projection variability, the first goal of this paper was to investigate projection variability for projective content associated with 19 expressions of American English. The second goal was to explore the hypothesis, called the Gradient Projection Principle, that content projects to the extent that it is not at-issue. The findings of two pairs of experiments provide robust empirical evidence for projection variability and for the Gradient Projection Principle. We show that many analyses of projection cannot account for the observed projection variability and discuss the implications of our finding that projective content varies in its at-issueness for an empirically adequate analysis of projection.